Adapted Mother Wavelets for Identification of Epileptiform Complexes in Electroencephalograms - Popov, A.; Kanaykin, A.; Zhukov, M.; Panichev, O.; Bodilovsky, O. (Elektronika ir Elektrotechnika, 2010)
The task of constructing adapted mother wavelet function is examined with application to processing the electroencephalogram of epileptic brain. The new technique of creating mother wavelets adapted for the time localization of epileptiform complexes is proposed. The technique is based on the use of main eigenvectors of the matrix of averaged correlations for the predefined class of complexes. The experimental results shown 94 % of true localizations of complexes in real EEG signal.